Birds - Packard, Mary.; Brickman, Robin (Racine, Wis. : Western, 1992)
Answers many curious questions about birds and their behavior.
Formerly titled: I wonder how parrots can talk.
"A Golden book."
Includes index.
4.8
K-3
Keywords: Birds -- Juvenile literature; Questions and answers -- Juvenile literature; Birds; Questions and answers; Birds; Questions and answers